Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1046/j.1365-2915.1999.00187.x
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory responses to attractants and repellents in tsetse

Abstract: The aims of this study were to investigate how antennal olfactory cells of tsetse (Diptera: Glossinidae) code odour quality and how they are able to discriminate between attractive and repellent odours. For Glossina pallidipes Austen, a survey is presented of the cells' responses to attractive (1-octen-3-ol, acetone, 3-methylphenol, carbon dioxide) and repellent stimuli (2-methoxyphenol, acetophenone, lactic acid, naphthalene). In addition, the responses of these cells to binary mixtures and the dose-response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Of 7 types of sensillum analyzed here, all showed excitatory responses to 1-octen-3-ol except ab2, which showed no excitation to any odorants; 1-octen-3-ol emanates from tsetse hosts and attracts tsetse (27,28). We note that many antennal ORNs of 2 other tsetse species, G. fuscipes fuscipes and G. p. palpalis, also respond to 1-octen-3-ol (29)(30)(31), and 1-octen-3-ol has previously been found to elicit an increase in the field potential of the G. morsitans antenna in an electroantennogram study (32,33). There may have been great selective pressure to detect and evaluate the level of 1-octen-3-ol during the course of tsetse evolution; evidently, 1-octen-3-ol is a salient odorant for tsetse.…”
Section: Discussionmentioning
confidence: 68%
“…Of 7 types of sensillum analyzed here, all showed excitatory responses to 1-octen-3-ol except ab2, which showed no excitation to any odorants; 1-octen-3-ol emanates from tsetse hosts and attracts tsetse (27,28). We note that many antennal ORNs of 2 other tsetse species, G. fuscipes fuscipes and G. p. palpalis, also respond to 1-octen-3-ol (29)(30)(31), and 1-octen-3-ol has previously been found to elicit an increase in the field potential of the G. morsitans antenna in an electroantennogram study (32,33). There may have been great selective pressure to detect and evaluate the level of 1-octen-3-ol during the course of tsetse evolution; evidently, 1-octen-3-ol is a salient odorant for tsetse.…”
Section: Discussionmentioning
confidence: 68%
“…Nearly every medically relevant blood-feeding insect that transmits a disease-causing pathogen to humans detects and follows CO 2 gradients as part of its host-seeking behavior. In addition to the malaria mosquito Anopheles gambiae and the dengue/yellow fever mosquito Aedes aegypti, other CO 2 -loving hematophagous Diptera include tsetse flies (Voskamp et al, 1999) (sleeping sickness), black flies (Fallis and Raybould, 1975) (river blindness and filariasis), and sandflies (Pinto et al, 2001) (leishmaniasis). The reduviid bug Triatoma infestans, which transmits the trypanosome that causes Chagas' disease, also orients upwind to pulses of CO 2 (Barrozo and Lazzari, 2006).…”
Section: Co 2 -Evoked Behaviorsmentioning
confidence: 99%
“…Dose-response and sensitivity studies of non-pheromonal stimuli have been performed on several other Dipteran species, including: tsetse flies (Bogner 1992;Den Otter and van der Goes van Naters 1992;Voskamp et al 1999), Australian sheep blowflies (Park and Cork 1999), sandflies (Dougherty et al 1999), Queensland fruit flies (Hull and Cribb 2001), houseflies (de Weerdt and Kelling 2001;Kelling et al 2002), mosquitoes [C. pipiens: (Bowen 1990(Bowen , 1992 and A. gambiae: (Meijerink and van Loon 1999;Meijerink et al 2001)] and Drosophila (Clyne et al 1997;de Bruyne et al 1999de Bruyne et al , 2001Stensmyr et al 2003). However, no study has revealed the breadth of variation observed here with Rhagoletis flies, both within and among populations.…”
Section: Orn Variation In Sensitivitymentioning
confidence: 99%
“…The presence of ''antagonist'' ORNs at the periphery has also been examined in a study of tsetse flies (Voskamp et al 1999). Results showed that ''repellent'' compounds stimulated both ORNs specific to the ''repellents'', suggesting a labeled line neural pathway for behavior, as well as ORNs of a great variety of cell types, suggesting that repellents ''simultaneously activate many receptor types so that any olfactory information specific to host-finding is lost in the resulting barrage of sensory input''.…”
Section: Orn Sensitivity and Host Plant Shiftsmentioning
confidence: 99%
See 1 more Smart Citation